Non-Anticoagulant Activities of Low Molecular Weight Heparins-A Review - Ke Feng; Kaixuan Wang; Yu Zhou; Haoyu Xue; Fang Wang; Hongzhen Jin; Wei Zhao (MDPI AG, 2023)
Low molecular weight heparins (LMWHs) are derived from heparin through chemical or enzymatic cleavage with an average molecular weight (Mw) of 2000-8000 Da. They exhibit more selective activities and advantages over heparin, causing fewer side effects, such as bleeding and heparin-induced thrombocytopenia. Due to different preparation methods, LMWHs have diverse structures and extensive biological activities. In this review, we describe the basic preparation methods in this field and compare the main principles and advantages of these specific methods in detail. Importantly, we focus on the non-anticoagulant pharmacological effects of LMWHs and their conjugates, such as preventing glycocalyx shedding, anti-inflammatory, antiviral infection, anti-fibrosis, inhibiting angiogenesis, inhibiting cell adhesion and improving endothelial function. LMWHs are effective in various diseases at the animal level, including cancer, some viral diseases, fibrotic diseases, and obstetric diseases. Finally, we briefly summarize their usage and potential applications in the clinic to promote the development and utilization of LMWHs.